She speaks to me : Western women's view of the West through poetry and song - Stanford, Jill Charlotte; Green, Robin L. (Robin Lynn), 1954- (TwoDot, imprint of Rowman & Littlefield, 2016)
"This anthology of "Cowgirl" poets, and edited by Jill Charlotte Stanford (The Cowgirl's Cookbook, Keep Cookin' Cowgirl) features the words of a wide range of Western women poets chosen for this collection by real ranching women and cowgirls across the West as the poets whose words most speak to them and the Western experience" --